2019
DOI: 10.1093/nar/gkz780
|View full text |Cite
|
Sign up to set email alerts
|

A global functional analysis of missense mutations reveals two major hotspots in the PALB2 tumor suppressor

Abstract: While biallelic mutations in the PALB2 tumor suppressor cause Fanconi anemia subtype FA-N, monoallelic mutations predispose to breast and familial pancreatic cancer. Although hundreds of missense variants in PALB2 have been identified in patients to date, only a few have clear functional and clinical relevance. Herein, we investigate the effects of 44 PALB2 variants of uncertain significance found in breast cancer patients and provide detailed analysis by systematic functional assays. Our comprehensive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 58 publications
(95 reference statements)
9
68
0
Order By: Relevance
“…3d). This region is important for MutLα heterodimers formation, necessary for the correct mismatched DNA fragment excision [97]. The p.Val717Met (c.2149G > A) is a VUS that presents conflicting information of pathogenicity by ClinVar database and only AlignGVGD does not predict it as pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…3d). This region is important for MutLα heterodimers formation, necessary for the correct mismatched DNA fragment excision [97]. The p.Val717Met (c.2149G > A) is a VUS that presents conflicting information of pathogenicity by ClinVar database and only AlignGVGD does not predict it as pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Assays using HR as a read-out have emerged as the standard for the functional characterisation of VUS in BRCA1 and BRCA2 (Bouwman et al, 2013;Woods et al, 2016;Shimelis et al, 2017;Starita et al, 2018;Mesman et al, 2019). More recently, VUS in PALB2 have also been characterized in a similar manner (Figures 1, 2) (Park et al, 2014;Foo et al, 2017;Boonen et al, 2019;Rodrigue et al, 2019;Wiltshire et al, 2019). To identify variants that impact HR, the well described DR-GFP reporter, as well as the more recently introduced CRISPR-LMNA HR assay were used (Kass et al, 2013;Ducy et al, 2019).…”
Section: A Comprehensive Functional Analysis Of Vus In Palb2mentioning
confidence: 99%
“…PALB2-interacting proteins are depicted underneath their respective PALB2 interacting domain/regions. All PALB2 genetic variants from five functional studies (Park et al, 2014;Foo et al, 2017;Boonen et al, 2019;Rodrigue et al, 2019;Wiltshire et al, 2019) are shown and categorized per (functional) domain as benign (green framed sections), truncating (red framed sections), or VUS and synthetic missense variants (MVs) (blue framed sections) based on ClinVar. All functionally damaging PALB2 VUS with an HR efficiency < 50% compared to wild type PALB2 in at least one functional assay are highlighted in red.…”
Section: A Comprehensive Functional Analysis Of Vus In Palb2mentioning
confidence: 99%
See 2 more Smart Citations